Increase in the annual energy production due to a retrofit of vortex generators on blades. Issue 3 (12th November 2019) - Skrzypiński, Witold; Gaunaa, Mac; Bak, Christian; Junker, Birgit; Brønnum, Niels Bruhn; Kruse, Emil Krog
Abstract: The aim of the current work was to analyze the effect of retrofitting vortex generators (VGs) on the blades of a constant RPM, pitch‐regulated, megawatt‐sized turbine suffering from surface roughness. Engineering modelling and experimental work were utilized, indicating that the degradation of energy production may be mitigated by the VGs. The modelling results indicated that the optimal configuration of VGs to maximize the annual energy production (AEP) depends on the degree of severity of surface roughness. Depending on blade surface condition and turbine characteristics, installation of VGs on an incorrect blade span or installation of too large VGs too far out on the blade may cause loss in the AEP. Therefore, engineering modelling is necessary before VGs may be retrofitted on a specific turbine. The modelling results indicated that the worse blade surface, the more gain may be obtained from the VGs. The work included a full‐scale experimental validation of the present engineering model, lasting 27 months and comprising six turbines where VGs were mounted on three, each with a neighboring turbine as a reference. The turbines were analyzed in pairs, and the influence of the VGs was judged upon the relative difference in energy production before and after the installation. The reason was to limit measurement uncertainty. The results showed that all three turbines increased their energy production after the installation. Results from the three pairs showed an average increase in the energy production of 3.3%, being satisfactorily close to the average 2.8% predicted by the present engineering tool.